Apoptotic Computing: Programmed Death by Default for Computer-Based Systems. - Sterritt, Roy (Computer (00189162), 2011)
Inspired by the cellular self-destruct mechanisms in biological apoptosis, apoptotic computing offers a promising means to develop self-managing computer-based systems.